Pseudotumor Cerebri and Sickle Cell Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Three children, all girls, ages 9, 8, and 16 years, with sickle cell disease (SCD) presented with headache and were diagnosed with pseudotumor cerebri (PC) at the Children's National Medical Center, Washington, DC.